Update: The Ideology of Creativity - Hanson, Michael Hanchett (Farol, 2024)
Ten years ago I wrote Worldmaking: Psychology and the Ideology of Creativity, tracing the ideological functions of the concept over time. The world and the psychology of creativity have changed. From developmental, sociocultural, and complex systems perspectives, how can we understand and respond to the upheavals in the political, environmental, and technological landscapes, which are emerging alongside, destabilizing social fragmentation and intensified geo-political conflict?